USA and leftist regimes in Latin America: D. Trump administration approach - D. M. Rozental (Ибероамериканские тетради, 2019)
The article is devoted to the policy of the Donald Trump administration toward the leftist regimes of Latin America: Venezuela, Cuba and Nicaragua.Washington’s strategy and tactics are examined, the reasons for its diplomacy are determined.The efficiency of theUSAsanctions is evaluated.